AN INNOVATIVE APPROACH TO INTERDISCIPLINARY TEACHING OF TECHNICAL SCIENCES THROUGH REMOTE LABORATORY PLATFORMS - Abdullayeva N. I.; Haqberdiyeva N. O. (Web of Journals Publishing, 2026)
The article outlines the theoretical and methodological foundations for ensuring interdisciplinary continuity by implementing remote laboratories in teaching technical sciences. It analyzes how digital technologies, virtual simulators, IoT devices, and online laboratory platforms contribute to the integration of technical science content, the expansion of students' experimental activities, and the enhancement of independent learning efficiency. As a result of this research, a conceptual model for providing interdisciplinary integration based on remote laboratories has been developed.
Keywords: Remote laboratories, interdisciplinary continuity, technical education, STEM/STEAM, virtual simulators, IoT, conceptual model, digital transformation.